Electric-field-induced deformation and optical axis change by electroclinic effect in side-chain liquid-crystalline elastomers composed of polysiloxane backbone - Taira, Shiori; Hoshono, Yuka; Huruya, Kazushi; Minami, Hiroyuki; Hiraoka, Kazuyuki (Proceedings of Japanese Liquid Crystal Society Annual meeting, 2019)
Optical responses to electric stimulation in a monodomain side-chain SmA* elastomer have beeninvestigated. The electric-field-induced molecular tilt θM, caused by the electroclinic effect, was opticallyestimated in the SmA* phase. We observed the sample shrinkage along the layer normal was directlycoupled with the layer shrinkage caused by the electroclinic effect. θM, which is estimated to be 4° at -1.0V/μm, decreases with increasing field and reaches -4.5° at +1.0 V/μm after passing through the origin (0V/μm, 0°). On the other hand, the shear angle θE in shear deformation of the elastomer is estimated to beabout 0.08° – 0.09° in the E-field of +1.0 V/μm . The ratio of the tilt angle of the elastomer θE to themolecular tilt angle θM, namely, (θE /θM), is only about 0.02. The small ratio indicates that the tilt ofmesogens is indirectly coupled with the chain shape distribution of the polymer network in the elastomer,because the positional order of mesogens is liquid-like in smectic layers of the SmA*.